Introduction: Queer and Trans Issues in Medieval Drama - Stoyanoff, Jeffery G. (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2024)
This essay provides a landscape of queer and trans theoretical approaches, particularly as applied to medieval studies. Despite queer studies having been practiced since at least since the 1980s, medieval drama studies has seen fewer queer (and now trans) readings of medieval dramatic texts and bodies with few exceptions until recent years. Such approaches are more important now than ever given the ongoing assault against LGBTQIA individuals around the globe. Medieval drama is a fecund field for work in queer and trans studies, and through doing such work, we may indeed learn much about ourselves in the twenty-first century.